Leopardi e la Crestomazia della prosa. Note pedagogiche - Zedda, Michele (Studi sulla Formazione/Open Journal of Education, 2019)
Leopardi draws up an anthology of Italian prose entitled Crestomazia italiana della prosa where the educative purpose is very evident. The poet intends to educate the readers to national literature and to a good writing, but he proposes also a moral education, as the content of many extracts proves.